Analisis Limpasan Permukaan dengan Sistem Informasi Geografis untuk Mendukung Penentuan Indikator Kuantitatif Fungsi Hidrologi Das Cicatih - Muh Taufik (Jurnal Ilmu Pertanian Indonesia, 2006)
The Urban growth has proven give a significant effect on the hydrological watershed function. Information. Information about the impact on the water resource in such watershed could be spatially quantified using GIS tool. The response of Cicatih watershed in West Java to various scenarios was determined using SCS method. In the scenarios, the effect of an increase in settlement cover to surface runoff and water storage was examined. The results indicate that surface runoff increase to 79% and water storage decrease to 31% due to settlement expansion.